Study of Calcium Hydroxide (Ca(OH)2) and Sodium Bicarbonate (NaHCO3) Treatment Through The Dynamics of pH, COD, N/P Ratio Value and Plankton Abundance - Daruti Dinda Nindarwi (Journal of Aquaculture and Fish Health, 2019)
Environmental quality cultivation of considerable influence against the survival and growth of living beings in the water. Improvements to the environmental conditions of cultivation in order to remain stable and optimal for aquatic organisms, including fish as aquaculture animals become very necessary one, namely the granting of Ca(OH)2 (calcium hydroxide) and NaHCO3 (sodium bicarbonate). The application of Ca(OH)2 and NaHCO3 in fish farming serves as the buffer pH of pond water. In addition, the application of both these materials also function as degradation organic matter chemically, control the ratio N/P and the abundance of plankton in the water. This research aims to know the dynamics of the pH value, COD, N/P ratio and abundance of plankton by administering calcium hydroxide (Ca(OH)2) and sodium bicarbonate (NaHCO3) in the water. Methodology this research uses descriptive survey method or a method of research that aimed to describe existing phenomena, which takes place at the moment or the past. The results of the measurement of the pH value before the grant of Ca(OH)2 and NaHCO3 that is of 6.6-6.8 whereas after the grant of Ca(OH)2 and NaHCO3, there is increased and decreased range between 6.8-7.4. The results of the measurement of the value of COD prior to the grant of Ca(OH)2 and NaHCO3 that is ranged between 72.5-32.5 mg/l while the after grant of Ca(OH)2 and NaHCO3, there is increased and decreased ranged between 26-55 mg/l, results of measurement of the value of the ratio N/P before the grant of  Ca(OH)2 and NaHCO3 on all points of observation that is ranged between 3.15 – 3.68 while following the grant of Ca(OH)2 and NaHCO3, there is a decrease and an increase in the value of the ratio N/P a row ranges between 1.67 – 1.8 and 13.8 – 15.18. Observations a total density of plankton showed before the grant of Ca(OH)2 and NaHCO3 that is in the range 206.250-1.103.125 x104 ind/l whereas after the grant of Ca(OH)2 and there is a decrease in the density of NaHCO3 total plankton reach 9.375x104 ind/l. Research has been done gives the conclusion that the grant of Ca(OH)2 and NaHCO3 pH value can increase and may decrease the value of the COD. the ratio N/P and a density of total plankton. Suggestions for research is expected to do further research about the grant of Ca(OH)2 and NaHCO3 pH Dynamics against, COD, N/P ratio and abundance of plankton in summer.